Ultrasound and computed tomography guided fine needle aspiration cytology in diagnosing intra-abdominal and intra-thoracic lesions - Parahjuli, S; Tuladhar, A; Basnet, RB (Journal of Pathology of Nepal, 2011)
Background: Ultrasonography and computed tomography guided fine needle aspiration cytology has an important role in diagnosing intraabdominal and intrathoracic mass lesions. It has an accuracy of 70-90%, depending on the site under evaluation. Materials and Methods: This retrospective study was done in the Department of Pathology, Kathmandu Model Hospital, between June 2006 and November 2010. The study included 53 abdominal and 47 thoracic masses. The cytological diagnosis was correlated with clinical and radiological data to arrive at a final diagnosis. Results: Fine needle aspiration cytology was performed in various anatomic sites: liver (28 cases), pancreas (8 cases), lymph nodes (7 cases), ovary and gall bladder (3 cases each) and 2 cases each of gastrointestinal tract and omentum. Thoracic aspirations were done from the lung (44 cases) and mediastinum (3 cases). The most common malignancy encountered in the abdomen was hepatocellular carcinoma (12 cases). Non-small cell carcinoma was the most common diagnoses amongst the lung lesions (15 cases). Conclusion: Ultrasonography and computed tomography guided fine needle aspiration cytology had a high sensitivity and specificity in diagnosing deep seated lesions. Keywords: Computed tomography; Deep-seated masses; Fine needle aspiration; Ultrasound DOI: 10.3126/jpn.v1i1.4444 Journal of Pathology of Nepal (2011) Vol.1, 17-21